Criminal characteristics of terrorism financing - Mikhalov, Serhii (Archives of Criminology and Forensic Sciences, 2025)
Terrorist financing should be viewed as a complex, dynamic system of actions and interactions carried out by individuals or groups with the aim of materially supporting terrorist activities. This process is not random or chaotic — on the contrary, it is carried out in a specific logical sequence aimed at achieving terrorist objectives. Such actions leave certain traces, both in the physical environment and in the information space, as well as in the minds of individuals who participate in financial transactions or may witness these events. The mechanism of terrorist financing consists of a number of key elements, which in criminalistics are identified with the mechanism of criminal activity and, based on the results of generalization and systematization, take the form of a criminalistic characteristic. The purpose of the article is to determine the characteristics of the criminalistic characteristics of terrorist financing. It has been determined that the criminalistic characteristics of terrorist financing are a systematized set of typical features that reflect the most common methods of committing this type of criminal activity. Its main purpose is to provide pre-trial investigation authorities with structured information that allows them to identify typical traces in a timely manner, reconstruct financing schemes, predict the further actions of participants, and select the most effective investigative methods. In general, understanding the mechanism of terrorism financing as a separate criminalistic category, as well as knowledge of its main elements, significantly increases the effectiveness of investigations. This helps to organize the evidence gathered, form a logically structured evidence base, and allows for a comprehensive analysis of the facts in cases involving the financing of terrorist activities.